The Symbolic Meaning of Malay Proverbs from Sambas, West Kalimantan - Zulfahita Zulfahita; Gunta Wirawan; Sofia Nur Havizah; Eti Sunarsih; Safrihady Safrihady; Lili Yanti; Wahyuni Oktavia; Sri Mulyani (Aksara, 2026)
Amidst the rapid onslaught of modernisation and globalisation offering popular culture, Sambas Malay proverbs face the challenge of remaining relevant and understandable to the younger generation. Every day, the younger generation is presented with external content that is far removed from their own cultural roots. This phenomenon is truly concerning because it is feared that it will erode local culture. Therefore, it is considered necessary to conduct in-depth studies on the oral traditions of the community, including proverbs, especially in uncovering the layers of symbolic meaning contained within proverbs. This study aims to describe the symbols and meanings of Sambas Malay proverbs from West Kalimantan. The method used in this study is descriptive qualitative with a semiotic approach. The data sources in this study were obtained from informants, namely cultural observers, traditional leaders, and community leaders who are native speakers of the Sambas Malay language totaling 12 people. The data collection techniques used were interview techniques, observation, documentary analysis, and Focus Group Discussion (FGD) with data analysis techniques, namely (1) data reduction, (2) data presentation, and (3) drawing conclusions/verification. The results of the study show that Sambas Malay proverbs can be classified as follows: (1) symbols of human anatomy, namely body parts such as elbows, hair, head, hands, face, etc., as well as human nature, character, and temperament; (2) symbols of animal’s symbols of animals, such as roosters, mice, sharks, monkeys, snakes, cows, etc.; (3) plant symbols, such as sugar cane leaves, coconut shells, tree stumps, tuba, taro, etc.; (4) natural symbols, such as water, earth, soil, day, night, etc.AbstrakPenelitian ini bertujuan untuk mendeskripsikan simbol dan makna peribahasa Melayu Sambas Kalimantan Barat. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan pendekatan semiotika. Sumber data dalam penelitian ini didapat dari informan yaitu budayawan, tokoh adat, dan tokoh masyarakat yang merupakan penutur asli bahasa Melayu Sambas yang berjumlah 12 orang. Adapun teknik pengumpulan data yang digunakan yaitu Teknik wawancara, observasi, analisis dokumenter, dan Focus Group Discussion (FGD) dengan Teknik analisis data yaitu (1) reduksi data, (2) penyajian data, dan (3) penarikan simpulan/verifikasi. Hasil penelitian menunjukkan bahwa peribahasa Melayu Sambas diklasifikasikan, sebagai berikut: (1) simbol-simbol anatomi manusia, yaitu anggota tubuh seperti siku, rambut, kepala,  tangan, wajah, dan lain-lain, serta sifat, watak, dan perangai manusia; (2) simbol-simbol hewan, seperti ayam Jantan, tikus, hiu, monyet, ular, sapi, dan lain-lain; (3) simbol-simbol tumbuhan, seperti daun tebu, tempurung, tunggul kayu, tuba, keladi, dan lain-lain; (4) Simbol-simbol alam, seperti air, tanah, tanah, siang, malam, dan lain-lain.